The Creation of a Hub for Ukrainian Intangible Cultural Heritage: A Case Study of the Ivan Honchar Museum - Hrymych, Maryna; Vertiuk, Myroslava; Levchenko, Andrii (Ethnologies, 2023)
We focus on the Ivan Honchar Museum National Centre of Folk Culture and three of its projects aimed at collecting, safeguarding, restoring, and promoting ICH (“Night of Traditional Dance,” “Kobzar Pentecost Festival” and “Oreli”). Having assembled one of the best collections of folk art and traditional material culture in Ukraine, the Ivan Honchar Museum has become a solid hub not only of tangible, but also intangible heritage, including oral traditions, arts, games, crafts, feasts, song, music, dance, and rituals. The article describes the circumstances in which folk singing, folk dance, and folk instrumental music can generate projects for successful folk festivals. In our times, the safeguarding of ICH means not only collection and archiving, but also support and promotion of its carriers, ensuring reproduction and transmission, developing consumers for this segment of culture, and involving children and youth.